2023
DOI: 10.20870/oeno-one.2023.57.1.7273
|View full text |Cite
|
Sign up to set email alerts
|

Identification of grape berry indigenous epiphytic yeasts with <i>in vitro</i> and <i>in vivo</i> antagonistic activity towards pathogenic fungi

Abstract: During their lifespan, grapes are exposed to conditions that can endanger plant health, including fluctuating climate and infection by pests and insects. In particular, attacks by filamentous fungi represent huge annual losses for grape farmers. Present concerns about rising antimicrobial resistance, fungicide prohibitions and shifting consumer tastes are driving the search for less harmful ways of preventing damage to grapevine by pathogenic fungi. In this study, the antagonist activity of yeasts isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…However, the seed epiphytes can become endophytes by entering the seed through the small pores of the seed coat, and vice versa [18]. Also, the epiphytes can provide the rst host defense against external pathogens and antagonize other species with in the microbial population [21,22]. Therefore, understanding the epiphytic and endophytic seed microbiome can be expected to provide insight into the formation and interactions of the seed microbiome [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the seed epiphytes can become endophytes by entering the seed through the small pores of the seed coat, and vice versa [18]. Also, the epiphytes can provide the rst host defense against external pathogens and antagonize other species with in the microbial population [21,22]. Therefore, understanding the epiphytic and endophytic seed microbiome can be expected to provide insight into the formation and interactions of the seed microbiome [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial fungicides, based on Biological Control Agents (BCAs), such as bacteria, yeasts, and molds, represent a valid alternative to chemicals for a safer and more effective control strategy [ 16 , 17 , 18 , 19 , 20 ]. Most of the BCAs described against post-harvest pathogens are non- Saccharomyces yeasts [ 21 , 22 , 23 , 24 , 25 ], because they offer advantages, such as simple nutritional requirements, the ability to colonize dry surfaces for long periods and the inability to produce allergenic spores or mycotoxins. In 1996, Rhodotorula glutinis (Fresen.)…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing view that under favorable ecological conditions, the grape natural microbial ecosystem can remain relatively stable, and the dynamic and balanced interactions between microbes and between grapes and microbes can ensure growth health and material accumulation [16,17]. It has also been found that the presence and metabolic activity of certain organisms on the grape epidermis may antagonize other species, while bioactive molecules secreted by endophytic and phyllosphere yeasts can also replace the action of essential agrochemicals [18]. Moreover, natural yeasts may have biocontrol activity against filamentous fungi.…”
Section: Introductionmentioning
confidence: 99%